Differences in rituximab use between pediatric rheumatologists and nephrologists for the treatment of refractory lupus nephritis and renal flare in childhood-onset SLE - Mileka Gilbert; Beatrice Goilav; Joyce J. Hsu; Paul J. Nietert; Esra Meidan; Annabelle Chua; Stacy P. Ardoin; Scott E. Wenderfer; Emily von Scheven; Natasha M. Ruth; for the Pediatric Nephrology and Rheumatology Collaborative Group, the Childhood Arthritis and Rheumatology Research Alliance, and the American Society for Pediatric Nephrology (BMC, 2021)
Abstract Background Consensus treatment plans have been developed for induction therapy of newly diagnosed proliferative lupus nephritis (LN) in childhood-onset systemic lupus erythematosus. However, patients who do not respond to initial therapy, or who develop renal flare after remission, warrant escalation of treatment. Our objective was to assess current practices of pediatric nephrologists and rheumatologists in North America in treatment of refractory proliferative LN and flare. Methods Members of Childhood Arthritis and Rheumatology Research Alliance (CARRA) and the American Society for Pediatric Nephrology (ASPN) were surveyed in November 2015 to assess therapy choices (other than modifying steroid dosing) and level of agreement between rheumatologists and nephrologists for proliferative LN patients. Two cases were presented: (1) refractory disease after induction treatment with corticosteroid and cyclophosphamide (CYC) and (2) nephritis flare after initial response to treatment. Survey respondents chose treatments for three follow up scenarios for each case that varied by severity of presentation. Treatment options included CYC, mycophenolate mofetil (MMF), rituximab (RTX), and others, alone or in combination. Results Seventy-six respondents from ASPN and foty-one respondents from CARRA represented approximately 15 % of the eligible members from each organization. Treatment choices between nephrologists and rheumatologists were highly variable and received greater than 50 % agreement for an individual treatment choice in only the following 2 of 6 follow up scenarios: 59 % of nephrologists, but only 38 % of rheumatologists, chose increasing dose of MMF in the case of LN refractory to induction therapy with proteinuria, hematuria, and improved serum creatinine. In a follow up scenario showing severe renal flare after achieving remission with induction therapy, 58 % of rheumatologists chose CYC and RTX combination therapy, whereas the top choice for nephrologists (43 %) was CYC alone. Rheumatologists in comparison to nephrologists chose more therapy options that contained RTX in all follow up scenarios except one (p < 0.05). Conclusions Therapy choices for pediatric rheumatologists and nephrologists in the treatment of refractory LN or LN flare were highly variable with rheumatologists more often choosing rituximab. Further investigation is necessary to delineate the reasons behind this finding. This study highlights the importance of collaborative efforts in developing consensus treatment plans for pediatric LN.